Freshwater Bacterioplankton Metacommunity Structure Along Urbanization Gradients in Belgium - Hanashiro, Fabio Toshiro T.; Mukherjee, Shinjini; Souffreau, Caroline; Engelen, Jessie; Brans, Kristien I.; Busschaert, Pieter; De Meester, Luc (Frontiers in Microbiology, 2019)
Urbanization is transforming and fragmenting natural environments worldwide, driving changes in biological communities through alterations in local environmental conditions as well as by changing the capacity of species to reach specific habitats. While the majority of earlier studies have been performed on higher plants and animals, it is crucial to increase our insight on microbial responses to urbanization across different spatial scales. Here, using a metacommunity approach, we evaluated the effects of urbanization on bacterioplankton communities in 50 shallow ponds in Belgium (Flanders region), one of the most urbanized areas in Northwest Europe. We estimated the relative importance of local environmental factors (35 abiotic and biotic variables), regional spatial factors and urbanization (built-up area) quantified at two spatial scales (200 x 200 m and 3 x 3 km). We show that urbanization at local or regional scales did not lead to strong changes in community composition and taxon diversity of bacterioplankton. Urbanization at regional scale (3 x 3 km) explained only 2% of community composition variation while at local scale (200 x 200 m), no effect was detected. Local environmental factors explained 13% (OTUs with relative abundance ≥0.1%) to 24% (12 dominant OTUs - ≥1%) of community variation. Six local environmental variables significantly explained variation in bacterioplankton community composition: pH, alkalinity, conductivity, total phosphorus, abundance of Daphnia and concentration of copper (Cu), of which pH was partly mediated by urbanization. Our results indicate that environmental rather than spatial factors accounted for the variation in bacterial community structure, suggesting that species sorting is the main process explaining bacterioplankton community assembly. Apparently, urbanization does not have a direct and strong effect on bacterioplankton metacommunity structure, probably due to the capacity of these organisms to adapt towards and colonize habitats with different environmental conditions and due to their fast adaptation and metabolic versatility. Thus, bacterioplankton communities inhabiting shallow ponds may be less affected by environmental conditions resulting from urbanization as compared to the impacts previously described for other taxa.